An Organizational Assessment of 34 Home Delivered Meals Programs that Engaged and Assisted Homebound Individuals With Obtaining the COVID-19 Vaccine During the Pandemic. (July 2023) - Guglielmo, Dana; Cloud, Jennifer; Trejo, Laura; Baca, Chris; Smith, Lisa V.; Shetgiri, Rashmi; Kuo, Tony; ,
Vaccinating homebound individuals during the COVID-19 pandemic presented several challenges, including time and cost of engaging this group. In Los Angeles County, the departments of Public Health and Aging and Disabilities turned to home delivered meals programs (HDMs) for help with this public health priority. A mixed-method organizational assessment of 34 HDMs was conducted during March–April 2022 to describe these efforts. Most HDMs were nonprofit (67.6%) and had <25 staff (58.8%). Overall, they served a large catchment area before and during COVID-19, providing services to an estimated total of 24, 995 clients/week and delivering 19, 511 meals/day. A majority (82.4%) reported engaging their clients to facilitate COVID-19 vaccinations. As of early 2022, <6% of these HDMs' homebound clients were unvaccinated. These programs' efforts to assist older individuals who were homebound during the pandemic represent a potentially underutilized model of public-nonprofit/not-for-profit partnership for improving vaccine delivery and uptake in this hard-to-reach population.